Dimensions of the Pedestrians' Personal Territory in the "New Bendar 45" Urban Area in Manado – North Sulawesi, Indonesia - Olivia Moningka; Sumarni Hamid Aly; Mubassirang Pasra; Muhammad Isran Ramli (Nusantara Science and Technology Proceedings, 2022)
The New Bendar 45 area in Manado - North Sulawesi is a shopping and office center that provides territories or spaces for pedestrians. This research, therefore, aims to determine the dimensions of the pedestrian's personal territory by observing their behaviors at the location in the morning, afternoon, and evening with the use of video and photo cameras. Person-centered Mapping technique was used for the analysis with the help of AutoCAD program. There are 17 dimensions of pedestrian's personal territories found, each with varying behavioral characteristics. These results are therefore useful as a reference when planning the pedestrian space requirements in the urban areas.